"Because it eases my Childbirth Plan": a qualitative study on factors contributing to preferences for caesarean section in Thailand - Sasitara Nuampa; Ameporn Ratinthorn; Pisake Lumbiganon; Somporn Rungreangkulkij; Nilubon Rujiraprasert; Natthapat Buaboon; Nampet Jampathong; Alexandre Dumont; Claudia Hanson; Myriam de Loenzien; Meghan A. Bohren; Ana Pilar Betrán (BMC, 2023)
Abstract Background Although caesarean section (CS) rates have increased rapidly in Thailand, the upward trend is not supported by significant maternal or perinatal health benefits. The appropriate use of CS through QUALIty DECision-making by women and providers (QUALI-DEC project) aims to design and implement a strategy to optimize the use of CS through non-clinical interventions. This study aimed to explore the factors influencing women's and health professionals' preferences for CS delivery in Thailand. Methods We conducted a formative qualitative study by using semi-structured in-depth interviews with pregnant and postpartum women, and healthcare staff. Purposive sampling was used to recruit participants from eight hospitals across four regions of Thailand. Content analysis was used to develop the main themes. Results There were 78 participants, including 27 pregnant and 25 postpartum women, 8 administrators, 13 obstetricians, and 5 interns. We identified three main themes and seven sub-themes of women and healthcare providers' perceptions on CS: (1) avoiding the negative experiences from vaginal birth (the pain of labor and childbirth, uncertainty during the labor period); (2) CS is a safer mode of birth (guarantees the baby's safety, a protective shield for doctors); and (3) CS facilitates time management (baby's destiny at an auspicious time, family's management, manage my work/time). Conclusions Women mentioned negative experiences and beliefs about vaginal delivery, labor pain, and uncertain delivery outcomes as important factors influencing CS preferences. On the other hand, CS is safer for babies and facilitates multiple tasks in women's lives. From health professionals' perspectives, CS is the easier and safer method for patients and them. Interventions to reduce unnecessary CS, including QUALI-DEC, should be designed and implemented, taking into consideration the perceptions of both women and healthcare providers.